Dasatinib in chronic myeloid leukemia: a review - Dolly G Aguilera; Apostolia M Tsimberidou (Dove Medical Press, 2009)
Dolly G Aguilera1, Apostolia M Tsimberidou21Department of Hematology-Oncology and Stem Cell Transplantation, Children’s Memorial Hospital, Northwestern University, Chicago, IL, USA; 2Department of Investigational Cancer Therapeutics, The University of Texas MD Anderson Cancer Center, Houston Texas USAAbstract: Deregulated BCR-ABL tyrosine kinase (TK) activity is the molecular marker for chronic myeloid leukemia (CML), which provides an identifiable target for developing therapeutic agents. Imatinib mesylate, a BCR-ABL TK inhibitor, is the frontline therapy for CML. Despite the stunning efficacy of this agent, a small number of patients develop a suboptimal response or resistance to imatinib. In newly diagnosed patients with chronic phase CML, the rate of resistance to imatinib at 4 years was up to 20%, increasing to 70% to 90% for patients in the accelerated/blastic phase. Resistance to imatinib led to the development of novel TK inhibitors such as dasatinib. Several clinical trials have reported more durable complete hematologic and cytogenetic responses with this agent in patients who are resistant or intolerant to imatinib. Dasatinib is well tolerated and has broad efficacy, resulting in durable responses in patients with any BCR-ABL mutation except for T3151 and mutations in codon 317 – most commonly F317L – including mutations that were highly resistant to imatinib, such as L248, Y253, E255, F359, and H396. Dasatinib is recommended for CML in chronic, blastic or accelerated phase that is resistant or intolerant to imatinib. Dasatinib was approved by the FDA at 100 mg once daily as the starting dose in patients with chronic phase CML and at 70 mg twice daily in patients with accelerated or blastic phase CML. Various clinical trial results provided evidence that resistance to one TK inhibitor can be reversed with the use of a different TK inhibitor (TKI). Other second-generation TKIs with activity in CML include nilotinib, bosutinib and INNO 406. New molecules, such as the inhibitor of Aurora family serine-threonine kinases, MK0457, which has antileukemic activity in CML associated with a T315I mutation, are being investigated. Allogeneic hematopoietic stem cell transplantation remains an option for selected patients.Keywords: dasatininb, chronic myeloid leukemia, BCR-ABL, tyrosine kinase inhibitor